Case study: Wisma Perbadanan Kemajuan Negeri Kedah Kedah Darul Aman / Mohammad Adam Asmadi ...[et al.] - Mohammad Adam, Asmadi; Mohd Arpaei, Ahmad Izzuddin; Mansor, Mohamad Farid; Abd Rahman, Nor Nadhirah; Aznan, Nur Syahirah (2015)
Our case study is Perbadanan Kemajuan Negeri Kedah. PKNK building concept is commercial and office building and PKNK building is one of the state building that is related to the goverment. The company that manages the building is Darulaman Aset Sdn. Bhd. They also have the maintenance department to maintain the buildings. Scope of work, the parties involved in maintenance aspect in Darul Aman Asset in PKNK building. Threrefore, at Wisma PKNK building, the maintenance activities was carried out under Wisma PKNK for budget provider and the inspection of building is carried out by Darulaman Asset Sdn.Bhd which is a wholly owned subsidiary of the PKNK. There is maintenance planning activities for each component of the building that was decided which is the schedule of inspection and also planner for the year. This building is an old building since 1965, PKNK building does’t have the CMMS system and BAS system. Beside for maintenance planning, the schedule system is being used by Darulaman Asset Sdn.Bhd inspector which include preventive maintenance and corrective maintenance will result a possible problems that will occur and can be avoided at the earlier stage of the defect that can reduce the maintenance cost.